Radiation-Induced Nonsteady-State Absorption in Multicomponent Silicate Glasses; Journal of Optical Technology; Vol. 71, № 2 - Arbuzov V. I.; Volchek A. O.; Gusarov A. I.; Lisitsyn V. M. Viktor Mikhailovich; Yakovlev V.Yu. (2004, 2004)
В фонде НТБ ТПУ отсутствует